"Building the Threads of Connection that We Already Have": The Nature of Connections via Technology for Older People. Issue 4 (8th August 2021) - Liddle, Jacki; Stuart, Avelie; Worthy, Peter; Levine, Mark; Kastelle, Tim; Wiles, Janet; Pachana, Nancy A.; Clare, Linda
ABSTRACT: Objectives : The social connectedness of older people is of increasing concern. Technology has been suggested for enhancing social inclusion. This study aimed to explore the nature and quality of connections via technology. Methods : Qualitative exploration of experiences, stories, and needs was undertaken through semi-structured interviews with older (7) and middle-aged (3) adults with rich experience of connections via technology in Australia and England. Core aspects of connections through technology were constructed through interpretive description analysis. Results : Four key aspects were: 1. The caliber of connections : descriptions of a range of subjective quality of connections and characteristics of good connections; 2. Experiences of poor connection ( mis- and dis-connection ) including descriptions of experiences creating isolation; 3. Reasons to connect described the purposes of technology-based connections including connecting with others, themselves and places important to them; 4. Making connections work described active strategies to enhance connection. Conclusions : Using technology is part of the social engagement of many people. Considering the related feelings of connection and support strategies and needs could enhance future research and practice with older people. Clinical implications : The different characteristics and potential positive and negative experiences of connection via technology need consideration in measuring social isolation and supporting older adults.